1999
DOI: 10.1017/s0140525x99002150
|View full text |Cite
|
Sign up to set email alerts
|

A model of saccade generation based on parallel processing and competitive inhibition

Abstract: During active vision, the eyes continually scan the visual environment using saccadic scanning movements. This target article presents an information processing model for the control of these movements, with some close parallels to established physiological processes in the oculomotor system. Two separate pathways are concerned with the spatial and the temporal programming of the movement. In the temporal pathway there is spatially distributed coding and the saccade target is selected from a “salience m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
556
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 667 publications
(599 citation statements)
references
References 327 publications
38
556
2
3
Order By: Relevance
“…While microsaccade rate, an indicator of when saccades occur, seems to be controlled supramodally, microsaccade direction as a measure of where saccades go clearly depends on the modality within which attention is shifted. Intuitively, where a saccade is oriented is determined later than the decision whether to make a saccade at all, a point of view that is also held by models of oculomotor control (e.g., Findlay and Walker 1999). Seemingly, the knowledge that shifts of visual attention or gaze are not required (as in AA) interferes with saccade programming at that later stage resulting in a weaker control of fixation stability in the purely auditory task.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While microsaccade rate, an indicator of when saccades occur, seems to be controlled supramodally, microsaccade direction as a measure of where saccades go clearly depends on the modality within which attention is shifted. Intuitively, where a saccade is oriented is determined later than the decision whether to make a saccade at all, a point of view that is also held by models of oculomotor control (e.g., Findlay and Walker 1999). Seemingly, the knowledge that shifts of visual attention or gaze are not required (as in AA) interferes with saccade programming at that later stage resulting in a weaker control of fixation stability in the purely auditory task.…”
Section: Discussionmentioning
confidence: 98%
“…We already concluded that overall microsaccade rate and microsaccade direction mirror different levels of interaction between attentional and oculomotor processes. Physiological studies (e.g., Carpenter 2000;Wurtz 1996) and theoretical models (e.g., Engbert et al 2002;Findlay and Walker 1999) suggest that the decision when a saccade program is initiated is earlier than where it will be oriented. We argued that the later stage may not be reached in situations which do not require visual attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the peripheral field of vision support exogenous triggering resulting in automatic saccades, while internal states support endogenous triggering resulting in intentional saccades (Liversedge, Gilchrist, & Everling, 2011). Findlay and Walker (1999) suggested that the simultaneous occurrence of exogenous and endogenous mechanisms might result in conflicts if working in opposite directions. Findings from Massen (2004) support the assumption of a parallel automatic and intentional generation of saccades, whereby only saccades with competitive advantages are performed.…”
Section: Saccade Generation In the Context Of Attentional Shiftsmentioning
confidence: 99%
“…Saccadic eye movements can be performed both in an automatic and a controlled manner (Findlay & Walker, 1999). Specifically, we wanted to explore saccades towards (prosaccades) or away from (antisaccades) sexually relevant or irrelevant targets as indicators of early attentional sexual information processing.…”
mentioning
confidence: 99%